We are here with you hands in hands to facilitate your learning & don't appreciate the idea of copying or replicating solutions. Read More>>

Looking For Something at vustudents.ning.com? Click Here to Search

www.bit.ly/vucodes

+ Link For Assignments, GDBs & Online Quizzes Solution

www.bit.ly/papersvu

+ Link For Past Papers, Solved MCQs, Short Notes & More


Dear Students! Share your Assignments / GDBs / Quizzes files as you receive in your LMS, So it can be discussed/solved timely. Add Discussion

How to Add New Discussion in Study Group ? Step By Step Guide Click Here.

+ How to Follow the New Added Discussions at Your Mail Address?

+ How to Join Subject Study Groups & Get Helping Material?

+ How to become Top Reputation, Angels, Intellectual, Featured Members & Moderators?

+ VU Students Reserves The Right to Delete Your Profile, If?


See Your Saved Posts Timeline

Views: 278

.

+ http://bit.ly/vucodes (Link for Assignments, GDBs & Online Quizzes Solution)

+ http://bit.ly/papersvu (Link for Past Papers, Solved MCQs, Short Notes & More)

+ Click Here to Search (Looking For something at vustudents.ning.com?)

+ Click Here To Join (Our facebook study Group)

Attachments:

Replies to This Discussion

Simplifying 7y + -60 = 12y 
Reorder the terms: -60 + 7y = 12y
Solving -60 + 7y = 12y
Solving for variable 'y'.
Add '-12y'
to each side of the equation.
-60 + 7y + -12y = 12y + -12y
Combine like terms: 7y + -12y = -5y -60 + -5y = 12y + -12y
Combine like terms: 12y +
-12y = 0
-60 + -5y = 0
Add '60' to each side of the equation.
-60 + 60 + -5y = 0 + 60
Combine like terms: -60 + 60 = 0
0 + -5y = 0
+ 60 -5y = 0 + 60
Combine like terms: 0 + 60 = 60
-5y = 60
Divide each side by '-5'. y = -12
Simplifying y = -12

RSS

© 2019   Created by + M.Tariq Malik.   Powered by

Promote Us  |  Report an Issue  |  Privacy Policy  |  Terms of Service

.